Assessment of perspectiveness of tree and shrub assortment in stands of general use of Saratov on the basis of sustainability to toxic exposure - A. V. Tereshkin; O. V. Solovieva; I. A. Mnekina (Новые технологии, 2018)
The analysis of green plantations in Saratov is presented. Studies have been conducted to reveal the resistance of leaf plates of common trees and shrubs to the effects of toxicants. Recommendations are given to expand the range of vegetation at the sites of plantings of the Saratov territory taking into account degree of gas stability.